2020
DOI: 10.2147/cmar.s231370
|View full text |Cite
|
Sign up to set email alerts
|

<p>LncRNA-SNHG16 Silencing Inhibits Prostate Carcinoma Cell Growth, Downregulate GLUT1 Expression and Reduce Glucose Uptake</p>

Abstract: Background: lncRNA-SNHG16 was identified as an oncogene in many cancers, but its involvement in prostate carcinoma is unknown. Material and Method: Expression of lncRNA-SNHG16 and glucose transporter 1 (GLUT-1) in 52 prostate carcinoma tissues and 36 normal prostate tissues was analyzed by RT-qPCR. Transfections were performed to analyze gene interactions. Cell proliferation was analyzed by cell proliferation assay. Results: Overexpression of lncRNA-SNHG16 effectively distinguished prostate carcinoma patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 19 publications
3
16
0
Order By: Relevance
“…Moreover, lncRNAs are tightly associated with therapeutic options and prognostic values of cancer patients (6). Here we observed SNHG16 was positively associated with gastric cancer, consistently with previous reports (9,10). Results from this study indicate that SNHG16 is overexpressed in the tumor tissues of GC patients and high expression of SNHG16 is associated with poor prognosis.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Moreover, lncRNAs are tightly associated with therapeutic options and prognostic values of cancer patients (6). Here we observed SNHG16 was positively associated with gastric cancer, consistently with previous reports (9,10). Results from this study indicate that SNHG16 is overexpressed in the tumor tissues of GC patients and high expression of SNHG16 is associated with poor prognosis.…”
Section: Discussionsupporting
confidence: 92%
“…For instance, studies reported that SNHG16 is high-expressed in colon cancer and regulated by the Wnt pathway (9). In addition, silencing SNHG16 inhibits prostate cell growth (10). Studies have uncovered a lncRNA-miRNA network where lncRNAs function as competitive endogenous RNAs (ceRNA) of miRNAs to recover the mRNA target genes expressions (11), suggesting the lncRNA-miRNA network is a potential target for anti-cancer therapy.…”
Section: Introductionmentioning
confidence: 99%
“…Recent research reports, SNHG16 over-expressed in PCa patients and play a role in promoting cell proliferation by regulating GLUT-1 expression and glucose uptake [10]. Here, we found SNHG16-incuded DU-145 cell proliferation, migration and invasion via up-regulating c-MYC, TGFBR2, E2F4, p-SMAD2, and p-SMAD3 expression.…”
Section: Discussionsupporting
confidence: 54%
“…1A). SNHG16 might play an important role in tumor progression [10]. In order to study the role of SNHG16 in PCa, we knocked down and overexpressed SNHG16 in DU-145 cells (Fig.…”
Section: The High Expression Of Snhg16 In Pca Tissues Promoted Tumor mentioning
confidence: 99%
See 1 more Smart Citation